2015
DOI: 10.1002/smll.201501283
|View full text |Cite
|
Sign up to set email alerts
|

Nanogap Electrodes towards Solid State Single‐Molecule Transistors

Abstract: With the establishment of complementary metal-oxide-semiconductor (CMOS)-based integrated circuit technology, it has become more difficult to follow Moore's law to further downscale the size of electronic components. Devices based on various nanostructures were constructed to continue the trend in the minimization of electronics, and molecular devices are among the most promising candidates. Compared with other candidates, molecular devices show unique superiorities, and intensive studies on molecular devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 154 publications
(224 reference statements)
1
58
0
Order By: Relevance
“…When data was only collected for positive bias voltages, as was the case for all the junctions not used in the molecular junction experiments in our study, we found that assuming a symmetric barrier (φ L = φ R ) produced better fits. While both symmetric and asymmetric barrier could be fitted to the I-V data to produce fits of visually similar quality (see Junction 3,7,8,13,and 22 in the data series presented in Supplementary Note 1), the values for barrier height for the case of symmetric barrier were more reasonable; when an asymmetric barrier was assumed, the two barrier heights were found to be comparable in most cases, but were very different in a few cases (e.g., 0.6 and 3.9 eV or 0.05 and 2.8 eV). The gap widths did not vary by more than 0.1 nm between the two barrier models unless the barrier heights were very different for the left and right electrodes like in the cases mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When data was only collected for positive bias voltages, as was the case for all the junctions not used in the molecular junction experiments in our study, we found that assuming a symmetric barrier (φ L = φ R ) produced better fits. While both symmetric and asymmetric barrier could be fitted to the I-V data to produce fits of visually similar quality (see Junction 3,7,8,13,and 22 in the data series presented in Supplementary Note 1), the values for barrier height for the case of symmetric barrier were more reasonable; when an asymmetric barrier was assumed, the two barrier heights were found to be comparable in most cases, but were very different in a few cases (e.g., 0.6 and 3.9 eV or 0.05 and 2.8 eV). The gap widths did not vary by more than 0.1 nm between the two barrier models unless the barrier heights were very different for the left and right electrodes like in the cases mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…P ractical molecular electronics based on solid-state devices will require the integration of arrays of interconnected molecular junctions into circuits and systems [1][2][3][4][5] . Before this becomes possible, new methodologies have to be developed for scalable and reproducible fabrication of nanogap electrodes featuring sub-3 nm wide gaps [6][7][8][9][10] . Mechanically controllable break junctions (MCBJs) 4,6,8,9,11,12 , scanning tunneling microscopy based break junctions (STM-BJ) 13,14 and electromigration breakdown junctions (EBJs) 15,16 made of gold are currently the most widespread nanogap electrodes used to realize molecular junctions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, metal nanogaps have been reviewed with different specific focuses, such as on fabrication methods based on physical [39] or chemical methods, [40] various applications in specific areas, including electrodes, [41,42] molecular devices, [43,44] Compared with the relatively mature fabrication methods for nanogaps, sub-5 nm is a critical gap size that requires special methods to achieve. Moreover, many important properties and applications can only be achieved with sub-5 nm nanogaps, and the corresponding fabrication and devices are more challenging; thus, this area deserves more attention.…”
Section: Sub-5 Nm Metal Nanogapsmentioning
confidence: 99%
“…Previously, metal nanogaps have been reviewed with different specific focuses, such as on fabrication methods based on physical or chemical methods, various applications in specific areas, including electrodes, molecular devices, or plasmonic devices, and fabrication techniques for massive production . These reviews offer very good references for researchers and practitioners from a very specific perspective or from a broad view of metal nanogaps.…”
Section: Introductionmentioning
confidence: 99%